2008
DOI: 10.1007/s10832-008-9459-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear electromechanical behaviour of piezoelectric bimorph actuators: Influence on performance and lifetime

Abstract: Piezoelectric bimorph bender actuators find application number of areas, ranging from automotive to health care. High voltage operation in harsh environments poses ever more stringent demands on functionality and lifetime. In these high performance benders, the trade-off between functionality and lifetime becomes of increasing importance, and a model-based understanding is imperative for further tailoring actuator performance. An important issue in this is the non-linear electromechanical coupling and mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Van den Ende et al 35 measured the static deflection of a similar parallel bimorph, however, this cantilever was made of PZT5K material that had an even higher value of the piezoelectric charge constant, d 31 = −438 pm/ V. They measured the deflection with only one of the piezolayers activated, i.e., their reported deflection correlates to half of the full deflection that we report in Fig. 2.…”
Section: B Static Deflection and Resonance Frequencymentioning
confidence: 68%
See 1 more Smart Citation
“…Van den Ende et al 35 measured the static deflection of a similar parallel bimorph, however, this cantilever was made of PZT5K material that had an even higher value of the piezoelectric charge constant, d 31 = −438 pm/ V. They measured the deflection with only one of the piezolayers activated, i.e., their reported deflection correlates to half of the full deflection that we report in Fig. 2.…”
Section: B Static Deflection and Resonance Frequencymentioning
confidence: 68%
“…32,33 Yao et al 33 studied and modeled the nonlinear static response of piezoelectric materials and applied these models to calculate the deflection and blocking forces of various unimorph and bimorph cantilevers. Furthermore, van den Ende et al 35 recently reported on the effects of nonlinear stiffness when bimorphs are strained when operated in the parallel configuration when only a single piezolayer is actuated. These nonlinear effects are due to mechanical domain reorientation and a model was developed which incorporates the nonlinear stiffness of the passive piezolayer.…”
Section: A Design and Choice Of Piezomentioning
confidence: 99%
“…Designs based on piezoelectric materials have also been considered many times [9,15]. Most are based on bender type energy harvesters [9,17] using ceramic lead zirconate titanate (PZT) in a mass-spring system. This brittle ceramic is not practical to use in automobile tires unless elaborate stress transfer mechanisms are employed [9], requiring very tight manufacturing tolerances in order to function properly.…”
Section: Introductionmentioning
confidence: 99%
“…For the case of the active rigidity joint under adverse loading, all of these conditions are true-actuator stress-strain behavior extends into a nonlinear region, only one layer is active instantaneously, and arbitrary actuator embedding is allowed. An iterative approach overcomes these obstacles similar to Ende et al (2008), another case where stiffness of at least one composite layer is dependent on strain. Rather than solving for the strains of equation ( 17) based on the solution to equations ( 15) and ( 16), an initial guess for actuator and upper face strains is made.…”
Section: 22mentioning
confidence: 99%